Treatment Effects and Posttreatment Follow-up of Miniscrew Anchorage-Supported Forsus FRD Appliance: Report of 2 Severe Class II Cases - Belma Işık Aslan; Emine Kaygısız; Ebru Küçükkaraca (Galenos Yayinevi, 2014)
This case report presents the treatment and posttreatment follow-up of 2 boys with severe skeletal Class II malocclusion with miniscrew anchorage-supported Forsus Fatigue Resistance Device (FRDMS). Miniscrews were inserted between the mandibular canine and first premolar root area bilaterally. The FRDMS treatment duration was 13 months in the first case and 11 months in the second case. The patients were treated with fixed orthodontic treatment afterward. The first patient was followed up for 1 year and 6 months and the second patient for 2 years and 8 months after fixed orthodontic treatment Essix retainers were worn fulltime for a period of 6 months and only at nighttime for the following 6 months in both cases after the fixed appliances. Lower incisor proclination was observed in both cases, although lower dentition anchorage was reinforced with miniscrews during Forsus FRD treatment. Favorable sagittal movement of the mandible was achieved in only 1 case. Overjet and molar correction were mainly at the dentoalveolar level in the other case. Occlusion was stable in the long-term.